A novel triazole as a rapidly acetate anion detector: synthesis, spectrophotometric, and TD-DFT studies - Makki, Sajjad Qasim; Balakit, Asim (Indonesian Journal of Chemistry and Environment, 2024)
A well- Sodium acetate has been used as a food flavor enhancer in the production of cheese, snack food, and pastry products. Hence, accurate quantification of sodium acetate content in food has significant importance within the realm of food chemistry. A Schiff-base reaction was used to produce the sensor 1,2,4 triazole derivative 3. The assessment of sensor 3's response to sodium salts (HSO4-, H2PO4-, NO2-, F-, Br-, Cl-, and AcO-) was conducted through naked-eye detection and subsequently confirmed using UV-vis spectroscopy. The addition of ions to sensor 3 resulted in a spectral change. Notably, only AcO- presented a unique shift in the visible spectra, while no changes were observed for the other anions. Sensor 3 has a notable level of sensitivity, as seen by the naked eye, in detecting acetate anion. The frequent addition of AcO- to a solution of sensor 3 results in an interesting color shift from light yellow to red-orange. The stoichiometry and association constant (Ka) were determined using the Benesi-Hildebrand equation, yielding values of 1:2 and 9.93x109 M-2, respectively. The calculation of the limit of detection (LoD) yielded a result of 6.86 µM. The synthesis of sensor 3 was confirmed using 1HNMR, IR, and UV techniques. The DT-DFT, HOMO, and LUMO values were computed using the Gaussian 09 software.